PERSPEKTIF KEPERAWATAN TRANS-BUDAYA: BUDAYA TRADISIONAL MASYARAKAT DAN PERAWAT TERHADAP PENYAKIT KUSTA DENGAN PENDEKATAN MODEL KEPERAWATAN TRANSKULTURAL DI KABUPATEN TUBAN - Prasetyo, Yoyok Bekti (Jurnal Bestari, 2009)
Professional nursing practices often experience constraint in giving service caused by cultural disparity between modern and traditional cultures. It causes less optimal services to the clients. Ignoring the existing culture will result on certain behaviors such as not taking care, accepting, and understanding clients' cultural background in expressing their feelings. Thus, it sometimes results conflict so that it will decrease nursing service quality. Moreover, from various health problems in Indonesia, leprosy generates various complex problems not only from medical but also from patients' mental and social aspects. Furthermore, there is still a stigma in society that leprosy is shameful contagion disease. So, this disease sufferer is isolated from local community. Some nurses are even suffering from phobia of the disease. Therefore, in order to neutralize negative stigma on the disease and even the nurses themselves, trans-cultural model theory approach can be used to unite traditional local cultural disparity and professional health system.